Evolutions of Oil Generation and Expulsion of Marine-Terrestrial Transitional Shales: Implications From a Pyrolysis Experiment on Water-Saturated Shale Plunger Samples - Fan, Qizhang; Cheng, Peng; Xiao, Xianming; Gai, Haifeng; Zhou, Qin; Li, Tengfei; Gao, Ping (Frontiers in Earth Science, 2021)
Shale reservoirs are characterized by self-generation and self-accumulation, and the oil generation and expulsion evolution model of organic-rich shales is one of important factors that obviously influence the enrichment and accumulation of shale oil and gas resources. At present, however, relevant studies on marine-terrestrial transitional shales are inadequate. In this study, a pyrolysis experiment was performed on water-saturated marine-terrestrial transitional shale plunger samples with type Ⅱb kerogen to simulate the evolutions of oil generation and expulsion. The results indicate that marine-terrestrial transitional shales have wider maturity ranges of oil generation and expulsion than marine and lacustrine shales, and the main stages of oil expulsion are later than those of oil generation, with corresponding Ro values of 0.85%–1.15% and 0.70%–0.95%, respectively. Although the oil generation and expulsion process induced a fractionation in compositions between the expelled and retained oils, both the expelled and retained oils of marine-terrestrial transitional shales are dominated by heavy compositions (resins and asphaltenes), which significantly differs from those of marine and lacustrine shales. The kerogen of marine-terrestrial transitional shales initially depolymerized to transitional asphaltenes, which further cracked into hydrocarbons, and the weak swelling effects of the kerogen promoted oil expulsions. The oil generation and expulsion evolutions of these shales are largely determined by their organic sources of terrigenous higher organisms. This study provides a preliminary theoretical basis to reveal the enrichment mechanism of marine-terrestrial transitional shale oil and gas resources.